Demographics, Clinical Characteristics, and Management of Idiopathic Intracranial Hypertension in Kuwait: A Single-Center Experience - Al-Hashel, Jasem Youssef; Ismail, Ismail Ibrahim; Ibrahim, Mohamed; John, John K.; Husain, Fatemah; Kamel, Walaa Ahmed; Behbehani, Raed; Ahmed, Samar Farouk (Frontiers in Neurology, 2020)
Background: Idiopathic intracranial hypertension (IIH) affects predominantly obese females during their reproductive age period. The demographics of this condition has not been studied in Kuwait before. Objectives: To determine the demographics, clinical features, risk factors and treatment modalities of IIH in the main neurology tertiary referral hospital in Kuwait and to compare our data with literature. Methods: A retrospective study was conducted to identify cases of IIH seen between 1 January 2017 and 31 December 2018. Patients were diagnosed in and referred from the neurology and neuro-ophthalmology clinics. Results: Our cohort consisted of 139 patients. We estimated a crude annual incidence rate of IIH of 3.28 per 100,000 population. Female-to-male ratio was 9.6:1. Mean age was 32.1 ± 10.8 years. Mean age of males was 31.46 ± 12.63 and 32.11 ± 10.67 for females. The median of the duration from the first symptoms till diagnosis was 6 weeks (2 - 10 weeks). Headache was the most common symptom in 134 (96.4%) followed by visual disturbances in 85 (61.2%), transient visual obscurations (TVOs) in 84 (60.4%) patients, pulsatile tinnitus in 72 (51.8%) patients, diplopia in 22 (15.8%), other symptoms (e.g. nausea, vomiting, radicular neck and back pain) in 19 (13.7%) patients and one (0.7%) patient had facial weakness. High Body Mass Index (BMI) was seen in 89.9 % of patients, either overweight or obese, and it was the most common risk factors in both males (46.2%) and females (61.1%). Anemia was found in (38.1%), (21.6%)of patients used OCPs and (7.9%) used vitamin A. Bilateral transverse sinus stenosis (BTSS) was detected in 47 (33.8%) patients. Only 2 (1.4%) patients developed “fulminant IIH” characterized by rapidly-progressive disease. All the patients received medical treatment and only 12 (8.6%) needed surgical management. Conclusion: Incidence of IIH in Kuwait is similar to other regional studies but higher than western studies. Demographics and clinical features of IIH in our study are comparable to international and regional figures. Most of our patients had benign course. IIH is more prevalent in females and strongly associated with obesity.